A re‐examination of impulsive VLF signals in the night ionosphere of Venus - Russell C.T.; Singh R.N. (My University, 2025)
Singh and Russell (1986) reported that impulsive electrical signals observed by the Pioneer Venus Orbiter Electric Field Detector at all frequencies clustered about periapsis. However, the impulsive signals consist of both signals entering the instrument through the antenna and artificial pulses associated with telemetry errors as Taylor and Cloutier (1988) have pointed out. Obvious telemetry errors were not included in the original study but records of which signals were thought to be naturally occurring and which were thought to be telemetry noise were not kept. Thus we cannot check the original identifications on a point‐by‐point basis. We can, however, repeat the study and compare statistical results. This study indicates that there is naturally occurring noise in the dark ionosphere of Venus near periapsis as originally reported by Singh and Russell. However, the absolute rates of occurrence of the original study and the present work differ. Sometimes the rates are smaller and sometimes larger than originally reported. These differences may be due to the use of a higher threshold in the earlier study together with the lack of sufficient discrimination against telemetry dropouts. Our rates of “naturally occurring” emissions also differ from the non‐spike noise rates obtained by Taylor and Cloutier although our rates of artificial signals are similar. In any event the Singh and Russell study should not be used to infer the altitude distribution of the noise since the spacecraft spends more time at low altitude than high as it traverses the dark ionosphere. Copyright 1989 by the American Geophysical Union.